Same-sex unions in Islam - Jahangir, Junaid; Abdullatif, Hussein (My University, 2018)
The objective of this paper is to streamline the case for Muslim same-sex unions that was comprehensively made in Jahangir and Abdullatif (2016). Additionally, we try to address same-sex unions on the basis of non-binary gender, gender expression and sexual orientation. Based on our work, we argue that the case for Muslim same-sex unions can be made on the basis of broad principles of human dignity and affection and therefore through marriage or through the specific arguments of repelling harm and legal authority. In this regard, going beyond the overarching Islamic value of human dignity, we specifically argue that the case for same-sex unions can be anchored on verse 4:28 on facilitating a legal outlet for sexual expression.
Keywords: Islam and LGBTQ Muslims; Muslim same-sex unions; permanent celibacy; non-binary in Islam; homosexuality in Islam; Muslim gay marriage